Teachers’ perceptions of waste banks and their role in enhancing environmental quality within an ESD framework - Enggar Utari; Angsoka Dwipayana Marthaliakirana; Amalianneisha Rafadewi Andhanatami Putri; Alfi Ertando (JPBI (Jurnal Pendidikan Biologi Indonesia), 2026)
Background: Waste banks can serve as a practical strategy for implementing Education for Sustainable Development (ESD) in school-based environmental education. However, the effectiveness of their implementation is strongly influenced by teachers’ perceptions of how ESD principles can be integrated into learning activities. Objectives: This study examined teachers’ perceptions of the role of waste banks in improving environmental quality within the ESD framework. Methods: This study employed a sequential explanatory mixed-methods design, combining quantitative and qualitative approaches. Quantitative data were collected using a perception test instrument adapted from the New Environmental Paradigm (NEP) to reflect waste bank content across each indicator. Qualitative data were obtained through interviews with teachers. The population consisted of elementary, junior high, and high school teachers in Serang City. A total of 76 teachers were selected through purposive sampling, focusing on teachers in Cipare District, Serang City, due to the active management of waste banks in the area. Results: The quantitative findings showed that teachers demonstrated highly positive perceptions, with an average score of 90% across seven indicators: anti-anthropocentrism, fragility of nature’s balance, possibility of ecocrisis, rejection of exemptionalism, limits to growth, new society planning, and human technological capability. These findings were supported by interview data, which revealed that waste banks have primarily been implemented as part of environmental learning in schools. However, their implementation has not been explicitly designed based on ESD principles, and the integration of ESD values and dimensions into learning activities remains insufficiently systematic and clearly articulated. Conclusion: Teachers generally perceive waste banks as having strong potential to improve environmental quality and support environmental learning in schools. Nevertheless, their educational implementation has not yet fully reflected ESD principles in a structured and explicit manner. Therefore, stronger curricular integration, teacher capacity building, and more systematic incorporation of ESD values are needed to optimize the role of waste banks in fostering sustainable environmental education